Co-solvent selection for tocotrienol extraction from palm fatty acid distillate using supercritical carbon dioxide - Othman, Najwa; Chong, Gun Hean; Mohamad Azman, Ezzat; Suleiman, Norhidayah (Malaysian Palm Oil Board, 2022)
A predictive model was devised for the estimation of the Kamlet-Taft (KT) dipolarity/polarisability (π*) parameter for binary mixtures of supercritical carbon dioxide (scCO2) and co-solvent. The model allows the selection of the best co-solvent for the extraction of tocotrienols from palm fatty acid distillate (PFAD). Ethanol, acetone, and isopropanol were separately used as co-solvents in the range of 0.05 – 0.15 mL/g for the experimental set-up at 20 MPa and 53°C for 300 min and a CO2 flow rate of 32 ± 5 g/min. The model’s estimations of π* for all these binary mixtures followed the trends for the extraction of tocotrienols. The π* values increased with the concentration of co-solvent in the binary system and tocotrienol extraction was directly proportional to the π* value, but only up to a particular value. Of the three co-solvents tested, ethanol was predicted to be the best to enhance tocotrienol extraction. With a 0.075 mL/g of ethanol, the extraction yield was 30.03a ± 0.03 mg/g, more than that achieved with pure scCO2 (16.45b ± 2.02 mg/g).